SPIRITUAL CONTEXT OF MODULAR-DEVELOPMENTAL SYSTEMS OF EDUCATION, EDUCATION AND EDUCATION (Pedagogy of Higher and Secondary Education, 2007)
The article deals with the issues harmonious unity of spiritual context of modular-developing system, fundamental value of culture and education, valuable modular-developing process and teachers professional readiness.